Study The Effect Of Adding Some Types Of Food Stabilizers On The Quality Parameters Of Persimmons Kaki Leathers. (Damascus University Journal of agriculture sciences, 2021)
This research was conducted at Department of Food science, Faculty of Agriculture, Puree persimmons were used to prepare dried persimmon leathers, The research aimed to study the effect of Some Of Types Food Stabilizers (maltodextrin, arabic gum, pectin) on some quality Parameters for persimmons dried leathers by hot air at a temperature of 60º C to a moisture content of not more than 20%.The results showed persimmon leather dried Additive to it maltodextrin, had  maintained a higher content of total phenols, beta-carotene and vitamin C, which reached (11.17 mg / 100 g  dry weight, 111.23 μg/100g , 12.16 mg / 100 g) respectively.these samples also showed their a noticeable highier in the antioxidant activity Estimated in way (DPPH, FRAP) (80.04% ,87.21%) respectively.
Keywords: Persimmon Kaki Leather; Maltodextrin; Arabic Gum; Pectin Hot Air Drying; Chemical Indicators; Active Biological Compounds